Impact of apical extent of root canal filling on vertical root fracture: a case–control study. (20th May 2019) - PradeepKumar, A. R.; Shemesh, H.; van Loveren, C.; JothiLatha, S.; Shireen, F.; VijayaBharathi, R.; Kishen, A.
Abstract: Aim: To investigate the impact of apical extent of root filling on vertical root fracture (VRF) in a case–control study. Methodology: Eighty‐six patients (119 roots) diagnosed with VRF in crowned root filled anterior and posterior teeth were selected. The cases were matched individually with control teeth in a ratio of 1:1 for age (±5 years), gender, tooth type, canal instrumentation method, master apical file (MAF) size and taper, technique of canal filling and time period after root filling. All root canals had been prepared using nickel–titanium (NiTi) rotary instruments and filled using the lateral compaction technique. The apical extent of root filling (overfilled to or beyond the radiographic apex or not overfilled and short of the radiographic apex) was recorded as the dependent variable by two individual examiners. Inter‐examiner agreement was obtained using Kappa statistics. Recorded numbers of overfilled and not overfilled canals in cases and controls were analysed using chi‐square tests and conditional logistic regression, and odds ratio was calculated. In addition, the frequency distribution of vertical and cross‐sectional extensions and the course of VRFs were evaluated. Results: The mean age of patients with VRFs was 50 ± 10 years with 27 (31%) males and 59 (69%) females. The Kappa score for inter‐observer agreement was 0.832 ( P  < 0.001). There was a significant difference between cases and controls with respect to apical extent of root filling ( P  < 0.0001). When compared to roots not overfilled, overfilled roots had 11.5 times higher odds for occurrence of VRF (OR = 11.5; CI: 4.99 – 26.48). Most VRFs had a complete corono‐apical longitudinal extension and were present bucco‐lingually/palatally. Conclusion: After matching for age, gender, tooth type, MAF size and taper, canal filling technique and time period after root filling, root canals filled to or beyond the radiographic apex following lateral compaction had a greater association with VRF than canals filled short of the radiographic apex.